RETRACTED: Cerebral Microbleed Detection via Convolutional Neural Network and Extreme Learning Machine - Lu, Siyuan; Liu, Shuaiqi; Wang, Shui-Hua; Zhang, Yu-Dong (Frontiers in Computational Neuroscience, 2021)
(Aim) Cerebral microbleeds (CMBs) are small round dots distributed over the brain which contribute to stroke, dementia, and death. The early diagnosis is significant for the treatment. (Method) In this paper, a new CMB detection approach was put forward for brain magnetic resonance images. We leveraged a sliding window to obtain training and testing samples from input brain images. Then, a 13-layer convolutional neural network (CNN) was designed and trained. Finally, we proposed to utilize an extreme learning machine (ELM) to substitute the last several layers in the CNN for detection. We carried out an experiment to decide the optimal number of layers to be substituted. The parameters in ELM were optimized by a heuristic algorithm named bat algorithm. The evaluation of our approach was based on hold-out validation, and the final predictions were generated by averaging the performance of five runs. (Results) Through the experiments, we found replacing the last five layers with ELM can get the optimal results. (Conclusion) We offered a comparison with state-of-the-art algorithms, and it can be revealed that our method was accurate in CMB detection